A PERIODICAL INVESTIGATION ON DOMESTIC AND FOREIGN TOURISTS VISITED CAPPADOCIA REGION (Third Sector Social Economic Review, 2020)
The aim of this study is examining the profile of domestic and foreign tourists came to Cappadocia. The variables such as overnight stays and mean of stay, choices of accommodation businesses, visiting periods and other variables of domestic and foreign tourists are examined periodically for 2015-2019. In this study, the data of the visitors who spent overnight stay in the accommodation businesses in Nevşehir, the region where the tourist attractions are the most intense in Cappadocia are examined. The data obtained from the Republic of Turkey Ministry of Culture and Tourism and it is tried to reach the results by analysing. It was determined that domestic tourists visited more than foreign tourists, the number of foreign tourists increased by years, and the mean of overnight of domestic and foreign tourists was relatively the same, and tourists visited Cappadocia in spring and summer mostly, in the period of 2015-2019 . In the same period, Ürgüp, center of Nevşehir, Avanos became the most preferred regions and the highest number of tourists came to Cappadocia from China, South Korea and Taiwan.
Keywords: Cappadocia; tourism; travel; tourist